2017
DOI: 10.1111/rda.12901
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mitochondrial uncoupling and glycolysis inhibition on ram sperm functionality

Abstract: Studies have demonstrated the importance of mitochondria to sperm functionality, as the main source of ATP for cellular homoeostasis and motility. However, the role of mitochondria on sperm metabolism is still controversial. Studies indicate that, for some species, glycolysis may be the main mechanism for sperm energy production. For ram sperm, such pathway is not clear. Thus, we evaluated ram sperm in response to mitochondrial uncoupling and glycolysis inhibition aiming to assess the importance of each pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
33
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 64 publications
0
33
0
4
Order By: Relevance
“…In addition, carnosine potentially inhibits the release of cytochrome c that leads to mitochondrial protection against damage (Baek et al, ). Carnosine is also a possible glycolysis inhibitor, since it could lead to mitochondrial dysfunction and oxidative imbalance (Losano et al, ). These data may have interfered in the motility results presented when the seminal sample was supplemented with the antioxidant.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, carnosine potentially inhibits the release of cytochrome c that leads to mitochondrial protection against damage (Baek et al, ). Carnosine is also a possible glycolysis inhibitor, since it could lead to mitochondrial dysfunction and oxidative imbalance (Losano et al, ). These data may have interfered in the motility results presented when the seminal sample was supplemented with the antioxidant.…”
Section: Discussionmentioning
confidence: 99%
“…Complementary in ram, Losano et al [9] demonstrated that mitochondrial depolarization did not affect total motility; however, sperm kinetic patterns were altered. On the other hand, they found that glycolytic pathway inhibition impaired total motility and sperm movement patterns.…”
Section: Introductionmentioning
confidence: 99%
“…;Bilodeau et al, 2001;Fernández-Santos et al, 2007; We verified that mitochondrial uncoupling [carbonyl cyanide 3 chlorophenylhydrazone (CCCP); 20, 40 and 80 µM] impairs ovine sperm kinetic patterns such as progressive motility (A), straight-line velocity (VSL; B) and linearity (LIN; C), indicating an essential role of mitochondria to sperm quality movement related to progressivity(Losano et al, 2017b). a,b Different letters on the bars indicate significant differences between treatments (P < 0.05).…”
mentioning
confidence: 75%